2008
DOI: 10.1093/hmg/ddn107
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic benefit derived from RNAi-mediated ablation of IMPDH1 transcripts in a murine model of autosomal dominant retinitis pigmentosa (RP10)

Abstract: Mutations within the inosine 5'-monophosphate dehydrogenase 1 (IMPDH1) gene cause the RP10 form of autosomal dominant retinitis pigmentosa (adRP), an early-onset retinopathy resulting in extensive visual handicap owing to progressive death of photoreceptors. Apart from the prevalence of RP10, estimated to account for 5-10% of cases of adRP in United States and Europe, two observations render this form of RP an attractive target for gene therapy. First, we show that while recombinant adeno-associated viral (AAV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…[3][4][5] In addition, therapeutic modalities have been demonstrated for other genetic subtypes of RP and LCA in a growing number of animal models, both of recessive and dominant forms of disease. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Notwithstanding such progress, the genetic complexity of this group of diseases represents a formidable logistic and economic hurdle in developing viable methods of prevention. Given this caveat, parameters effecting photoreceptor survival that are independent of the primary genetic lesion are critically important to identify.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In addition, therapeutic modalities have been demonstrated for other genetic subtypes of RP and LCA in a growing number of animal models, both of recessive and dominant forms of disease. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Notwithstanding such progress, the genetic complexity of this group of diseases represents a formidable logistic and economic hurdle in developing viable methods of prevention. Given this caveat, parameters effecting photoreceptor survival that are independent of the primary genetic lesion are critically important to identify.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for IMPDH1-adRP, a mutation-independent 'suppression only' strategy may potentially provide benefit as demonstrated at the histological level in an AAV-induced mouse model of IMPDH1-adRP. 51 In this study, AAV2/ 5-delivered mutant IMPDH was shown to induce a retinopathy in mice akin to RP. However, when co-injected with a second AAV expressing an siRNA targeting IMPDH, the outer nuclear layer thickness of co-injected mice at 4 weeks post-injection resembled wild-type outer nuclear layer thicknesses.…”
Section: Preclinical Studies Using Therapies Targeting the Primary Gementioning
confidence: 70%
“…Although degenerative retinopathies, including age-related macular degeneration (AMD), diabetic retinopathy, and RP represent major causes of world blindness, treatment options are currently exceedingly limited (15,(21)(22)(23)(24). No form of prevention is available for the nonexudative (dry) form of AMD, apart from dietary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…First, we chose a model of autosomal recessive RP, the IMPDH1 Ϫ/Ϫ mouse (14). These animals lack one of the two rate-limiting enzymes of de novo synthesis of GTP, a central mediator of visual phototransduction (15). With increasing age, these mice develop a mild retinopathy, as evidenced by decreases in electrophysiological readout from the retina in tandem with a thinning of the photoreceptor ONL in animals older than 10 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation